Amantadine and the Place of Acupuncture in the Treatment of Fatigue in Patients with Multiple Sclerosis: An Observational Study. Issue 1 (March 2013) - Foroughipour, Mohsen; Bahrami Taghanaki, Hamid Reza; Saeidi, Morteza; Khazaei, Mojtaba; Sasannezhad, Payam; Shoeibi, Ali
Background: Fatigue is a common symptom in patients with multiple sclerosis (MS). It has significant negative effects on the quality of life of patients with the condition. There are few therapeutic modalities for fatigue, which are also usually not sufficiently effective. The aim of this study was to evaluate the efficacy of acupuncture on this common symptom of patients with MS. Methods: In this before-and-after clinical trial, 40 patients with definite diagnoses of MS, according to the 'McDonald' criteria, were studied. Patients who had Expanded Disability Status Scale (EDSS) scores greater than 4, or who had another disease that could be potentially responsible for their fatigue, were excluded from the study. In all, 20 patients with fatigue refractory to amantadine underwent 12 sessions of acupuncture. Fatigue was scored according to the Fatigue Severity Scale (FSS). Results: A total of 15 (37.5%) patients with MS with fatigue responded to amantadine. The mean FSS score reduction after 2 months of treatment was 8±4, which was statistically significant (p<0.001). Of the 20 patients who were resistant to amantadine, 5 (25%) responded to acupuncture combined with amantadine treatment. The FSS scores of the 20 patients who were refractory were significantly reduced after this treatment (mean: 13±6, p<0.001). Conclusions: Acupuncture appears to be associated with benefits for a proportion of patients with fatigue who are resistant to conventional drugs such as amantadine, and this finding justifies further research.